The Influence of Social Media Influencers (SMIs) on Purchase Intention of Sunscreen Products - Nabila Jihan Authalia; Albari Albari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to explain the influence of social media influencers (SMIs) on purchase intention with the object of research on sunscreen products. With the new paradigm due to rapid developments, the marketing world is encouraged to adapt and follow marketing trends using social media influencers (SMIs). In addition, the rampant cases of overclaiming sunscreen content that have occurred in Indonesia have made people more careful in buying sunscreen products through recommendations from social media influencers (SMIs). In this study, the sample used was 166 respondents throughout Indonesia, with a non-probability sampling technique and using the convenience sampling method. The analysis technique used in this study is Structural Equation Modeling (SEM) with analysis software, namely AMOS 26.0. The results of this study prove that there is a significant positive influence of the characteristics of social media influencers (SMIs) on the purchase intention of sunscreen products.